Effects of an Early Childhood Education and Care Prevention Program on Infant-Toddler Teacher Attributes: First Results of a Randomized Controlled Trial - Ortelbach, Niklas; Bovenschen, Ina; Gerlach, Jennifer; Scheithauer, Herbert (Early Education and Development, 2025)
Research Findings: After structural and process features of Early Childhood Education and Care (ECEC) quality were comprehensively studied in the past, recent research also included childcare teachers’ personal resources, knowledge, attitudes, and beliefs that may affect teacher-child interactions. The present randomized controlled trial aimed to investigate the effects of a universal preventive intervention program developed to promote attachment security and social-emotional development in ECEC settings. To examine the intervention effects at the teacher level, 125 German infant and toddler childcare teachers (age M = 34.0, 98 % female) reported their self-efficacy beliefs and job-related stress before, during, and after the implementation of the program. Multilevel models indicated that after completion of the program, teachers in the intervention group reported higher self-efficacy than did those in the waiting-control group (controlling for baseline scores). No significant effects on job-related stress were detected. Practice or Policy: Participating in a professional development program may impact infant-toddler teachers’ professional self-efficacy beliefs and, thus, contribute to promoting positive and sensitive teacher-child interactions. However, to reduce teachers’ job-related stress, programs with a clearer focus on mental well-being may be indicated in addition to policy actions to improve structural working conditions in the ECEC context.
CRIS-Team Scopus Importer:2025-05-23